Cash Flow Volatility and Capital Structure in The Indonesia Mining Sector: The Moderating Role of Fixed Assets Listed on The Indonesian Stock Exchange 2018-2023 - Shendy Alifya Budiastuty; Justina Ade Judiarni (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of cash flow volatility on capital structure and to examine the moderating role of fixed assets in the mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The study employs a quantitative approach using secondary data obtained from the annual financial statements of mining companies. The population consists of all mining firms listed on the IDX, while purposive sampling is applied to select companies that meet specific criteria, resulting in a sample of 57 firms observed over five years. Capital structure is used as the dependent variable, while cash flow volatility serves as the independent variable. Data analysis is conducted using panel data regression with the Fixed Effect Model (FEM) through EViews 12 software. The results indicate that cash flow volatility has a positive and significant effect on capital structure. However, fixed assets exhibit a negative but insignificant moderating effect on the relationship between cash flow volatility and capital structure. These findings suggest that higher fluctuations in operating cash flows increase firms’ reliance on debt financing. Therefore, effective cash flow management and optimal utilization of fixed assets are essential to maintaining a healthy capital structure